Être élève en Iran au tournant des années 1900 : les écoles de l’Alliance israélite universelle - Alice Bombardier; Leila Koochakzadeh (Revue des Mondes Musulmans et de la Méditerranée)
Taking an interest in the actors of the school, in their experiences, and in the modalities of teaching within local school systems in the Middle East, it is possible to renew the history of education in the region. The choice was made here to focus on a local but foreign school system in Iran, that of the “Alliance israélite universelle” (AIU) during the years 1898-1908, and to study within it: on the one hand, the profile and the daily life of the students; on the other hand, the mode of teaching French as a second language by the “direct method” and the knowledge acquired or representations that resulted from it. In a context of emerging new educational expectations, the AIU network has had many socio-political impacts in Iran and has been a direct source of inspiration for the new national schools.